Effectiveness of Hydroson Therapy (Hydrotherapy and Benson) and Dhikr Relaxation Therapy on Hemodynamic Function in the Elderly - Santi Damayanti; Cornelia Dede Yoshima Nekada (Gaster, 2023)
Background: The most common Non-communicable Diseases found in the elderly. Complementary therapy as a support for medical therapy is needed during a pandemic like today. Hydrotherapy soaked feet makes blood circulation smooth, Benson's relaxation and dhikr produce a relaxed condition so that it can increase endorphins hormones, increase vascular vasodilation and lower blood pressure, improve pulse rate and oxygen saturation Purpose :you knoweffectivenesshydroson therapy and dhikr relaxation therapy on hemodynamic function in the elderly. method: Type of quasi-experimental research with pre and post test design without control design, the sample size is 38 elderly who are Muslim and suffer from hypertension. Bivariate data analysis with Wilcoxon and paired T-test. Results :there was a difference in systolic blood pressure before and after being given hydrotherapy and Benson intervention with dhikr with a P value of 0.000. There was a difference in diastolic blood pressure before and after being given hydrotherapy and Benson's intervention with dhikr with a P value of 0.032. There was no difference in pulse frequency before and after being given the hydrotherapy and Benson interventions with dhikr with a P value of 0.221. There are differences in oxygen saturation before and after hydrotherapy and Benson intervention with dhikr with a P value of 0.004 Conclusion:Hydroson therapy and dhikr relaxation therapy are effective for hemodynamic function in the form of lowering blood pressure and increasing oxygen saturation in the elderly. But it has no effect on pulse frequency.